Keeping up, and keeping on: Risk, acceleration and the law-abiding driving offender: - Wells, Helen (Criminology & criminal justice, 2019)
Roads policing is the most likely generator of an adverse-outcome encounter between the general public and the police and is therefore one of the most likely situations in which individuals are confronted with their own ‘law-abidingness’, or lack of it. Despite this, it has so far failed to excite much criminological interest. The article will propose that the concepts of ‘risk’ (as a political as well as sociological concept) and ‘acceleration’ (of technological change, as well as everyday life) can be used to explain the controversial and apparently unsettling image of roads policing in recent years. This article reflects on how speeding offences (researched between 2002-2006) and mobile phone use by drivers (researched between 2013-2016) reveal much about how drivers see themselves, their priorities and the law.